Pengaruh Tax Avoidance terhadap Kinerja Perusahaan - Ainur Rokhmah (Akuntansi : Jurnal Akuntansi Integratif, 2019)
This study aims to address the problem formulation related to the effect of tax avoidance on the performance of manufacturing companies which are proxied by return on assets (ROA). The research method used is a quantitative approach with a causal or causal form. The research technique used is multiple regression analysis using SPSS Statistics Version 23. The number of samples in this  study were 97 company financial reports  from  a total population of 153 manufacturing company financial statements in 2017. The data used in this study are secondary data with Data is collected by means of documentation that is taking from the Indonesia Stock Exchange website and literature. This study found that tax avoidance has a negative effect on company performance, which means that the more companies reduce tax avoidan ce actions, it can improve company performance. This study also found that leverage has a negative effect on company performance, which means the higher leverage can reduce company performance.